A Study of Malaysian SMEs Awareness and Readiness on the Implementation of Goods and Services Tax (GST) - Liew, Swee Song (2010)
The impending introduction of Goods and Services Tax (GST) in Malaysia is expected to impact Malaysian businesses, particularly the Small and Medium Enterprises. Despite increasing recognition of the important role plays by SMEs, not much attention has been given to SMEs in relation to the GST introduction. Thus, aim of this study is to examine the SMEs state of awareness and readiness in adopting GST. A mixed research method was used to gather the sampled data. The findings indicated that the level of awareness and readiness among the respondents are low. This study managed to identify few determining factors which have humbled SMEs preparation in embracing GST.